Hadis Tahlili tentang Jumlah Raka`At Shalat Tarawih - Pairin Pairin (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
The growth of deeds after the Prophet died, because for the practice of worship solely to Allah swt. Various worship in Islam is more of a pious charity and spiritual practice in accordance with human nature. Implementation of worship is a regulation of the life of a Muslim, whether through the implementation of prayer, zakat, fasting and so forth. What is clear, the implementation of worship has united the Muslims in one goal, namely servitude to God alone. Through the worship of many things that many obtained by a Muslim whose interests not only cover the individual but broadly and universally important with sincere conditions and on the basis of obedience to Allah swt.From here, one of the most highly recommended worship of the Messenger of Allah, which is only done in the month of Ramadan is tarawih prayer. Tarawih prayers at first only said al-lail prayer because it is done especially on the night in the month of Ramadan. It is said tarawih (jama` from tarwihah word) because every two or four rakaat congregation of rest prayer is due to the length of the verses of the Qur'an which are read on every rakaat.Tarawih problem first and now is still an interesting topic to be studied, discussed and researched first, because there are some things that are still questioned by the ummah of Islam, among which is the number rakaat. In this case, the scholars are different opinions so that Muslims are also different in implementing it. The irony of the difference in this problem has occurred since the first Muslim generation since the days of the Companions, when they see firsthand the Prophet tarawih Messenger of Allah, at least they have obtained a direct explanation from him. Muslims among the laity become confused to choose and determine which is really true. While in the Muslim intellectuals more incentive to criticize by finding various reasons. And some assume that his opinion is the most correct, and people who do not agree with him actually think of him as a bid'ah expert. aka in a society, there is often unbalance between the Muslim groups with each other, because of differences in tarawih problems. To prevent such things from happening above, Muslims should develop their religious knowledge insight so as to grow mutual understanding between brothers and sisters.